Integration of Geriatrician Consultation for Trauma Admissions May Benefit Patient Outcomes. (June 2019) - Saha, Sumit; DiRusso, Stephen M.; Welle, Scott; Lieberman, Benjamin; Sender, Joel; Shabsigh, Ridwan; Baltazar, Gerard A.
Objective: Geriatric admissions to trauma centers have increased, and in 2013, our center integrated geriatrician consultation with the management of admitted patients. Our goal is to describe our experience with increasing geriatric fall volume to help inform organized geriatric trauma programs.Method: We retrospectively analyzed admitted trauma patients ≥65 years old, suffering falls from January 1, 2006, to December 31, 2017. We examined descriptive statistics and changes in outcomes after integration.Results: A total of 1, 335 geriatric trauma patients were admitted, of which 1, 054 (79%) had suffered falls. Falls increased disproportionately (+280%) compared with other mechanisms of injury (+97%). After 2013, patient discharge disposition to skilled nursing facility decreased significantly (–67%, p < .001), with a concomitant increase in safe discharges home with outpatient services. Regression analysis revealed association between integration of geriatrician consultation and outcomes.Discussion: Geriatrician consultation is associated with optimized discharge disposition of trauma patients. We recommend geriatrician consultation for all geriatric trauma activations.